2013
DOI: 10.1109/tdei.2013.6518964
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of surface charge on direct- fluorinated polyimide films

Abstract: Polyimide film, as a special type of engineering plastic film, is a kind of basic insulating material and is widely applied in the aerial, nuclear, microelectronic industry, turn to turn insulation and turn to ground insulation of inverter-fed motors. However, premature insulation failures occur frequently in motors with the disadvantage of pure PI inherent in all organic materials. The existence of surface charge has a great effect on breakdown characteristic and is the main reason leading to dielectric break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…19 Du has investigated the electrical properties of various polymers under different fluorinating conditions. 20,21 He finds that by fluorination, the corona resistant time is significantly improved and the partial discharge intensity is reduced. 22,23 However, most of the previous researches aim at the investigation on the direct fluorination using the unfilled pure epoxy resin samples, and fewer focused on Al 2 O 3 -filled epoxy resin which is wildly used as insulator materials in GIS or GIL.…”
Section: -2mentioning
confidence: 99%
“…19 Du has investigated the electrical properties of various polymers under different fluorinating conditions. 20,21 He finds that by fluorination, the corona resistant time is significantly improved and the partial discharge intensity is reduced. 22,23 However, most of the previous researches aim at the investigation on the direct fluorination using the unfilled pure epoxy resin samples, and fewer focused on Al 2 O 3 -filled epoxy resin which is wildly used as insulator materials in GIS or GIL.…”
Section: -2mentioning
confidence: 99%
“…The possible routes for the surface charge dissipation can be divided into the following three main patterns: lateral diffusion, recombination with the ions in the air and transfer through the bulk. Charge passing through the bulk of sample in a way of trapping and de-trapping is regarded as the dominant path of charge dissipation considering that the vertical electrical field built by the surface charges is much larger than the horizontal electrical field because of the thin thickness of the sample [20]. According to the decay curves of the surface potential, the decay process of the surface potential could be roughly divided into two stages.…”
Section: Surface and Volume Conductivitymentioning
confidence: 99%
“…The total thickness of the barrier dielectric was 0.37 mm. Surface fluorination of the dielectrics was carried out in a stainless reactor kettle with polytetrafluoroethylene lining at about 328 K (55 • C) using a F 2 /N 2 mixture with 20% F 2 by volume [22]. After evacuation and purification with nitrogen gas more than three times, the reactive gas mixture was introduced slowly into the vessel until the mixture pressure in the vessel had reached 0.05 MPa (500 mbar).…”
Section: Sdbd Devicementioning
confidence: 99%
“…For example, An et al [20,21] indicated that surface fluorination of PE has a significant influence on the charge injection and accumulation. Du et al [22,23] found that surface fluorination is an effective method for modulating the electrical properties and restraining the surface charge and space charge accumulation of the PI film.…”
Section: Introductionmentioning
confidence: 99%